2009
DOI: 10.1002/er.1588
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-fed solid oxide fuel cells for power generation-A review

Abstract: SUMMARYAmmonia has been identified as a promising sustainable fuel and hydrogen source for solid oxide fuel cells (SOFC). This paper aims to provide a literature review on ammonia-fed SOFCs. Both experimental studies and mathematical modeling investigations on NH 3 -fed SOFC are included and discussed. It is found that NH 3 is a technically feasible fuel for direct use in SOFCs and the performance of NH 3 -fed SOFC is comparable with that of the H 2 fed SOFC. Experimental study in literature also demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…Water is produced at the cathode therefore will not dilute the fuel. Research on ammonia SOFCs has been reviewed by Ni et al (2009). Ni also carried out modeling of ammonia SOFCs and it was found that increasing the inlet temperature of NH 3 -fueled SOFC is favorable for a higher electric output, but the temperature gradient in the SOFC is considerably higher, particularly near the inlet of the SOFC (Ni, 2011).…”
Section: Ammonia Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…Water is produced at the cathode therefore will not dilute the fuel. Research on ammonia SOFCs has been reviewed by Ni et al (2009). Ni also carried out modeling of ammonia SOFCs and it was found that increasing the inlet temperature of NH 3 -fueled SOFC is favorable for a higher electric output, but the temperature gradient in the SOFC is considerably higher, particularly near the inlet of the SOFC (Ni, 2011).…”
Section: Ammonia Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…where J 0 is the exchange current density, a is the symmetric factor (0.5 in the present study), z is the number of electrons involved in per electrochemical reaction (2 in the present study) [40][41][42].…”
Section: Electrochemical Modelmentioning
confidence: 99%
“…Solid oxide fuel cells (SOFCs) are more efficient than other traditional technologies for energy conversion from fuel to electricity due to their high operating temperature and straightforward power generation process [1][2][3][4][5]. SOFCs consist of 3 key layers: porous anode, dense electrolyte and porous cathode.…”
Section: Introductionmentioning
confidence: 99%